2017
DOI: 10.1038/tp.2017.117
|View full text |Cite
|
Sign up to set email alerts
|

Topologically convergent and divergent functional connectivity patterns in unmedicated unipolar depression and bipolar disorder

Abstract: Bipolar disorder (BD), particularly BD II, is frequently misdiagnosed as unipolar depression (UD), leading to inappropriate treatment and poor clinical outcomes. Although depressive symptoms may be expressed similarly in UD and BD, the similarities and differences in the architecture of brain functional networks between the two disorders are still unknown. In this study, we hypothesized that UD and BD II patients would show convergent and divergent patterns of disrupted topological organization of the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 90 publications
8
51
1
1
Order By: Relevance
“…These findings indicate that the aforementioned nodes are more integrated into the brain network of BD patients than in networks of individuals not suffering from BD, possibly leading to a disturbed perception of emotions in BD. Changes in the limbic system supporting our results were both found in resting‐state paradigms (Ambrosi et al, ; Anand et al, ; Lois, Linke, & Wessa, ; Wang, Wang, Jia, Zhong, Zhong et al, ) as well as in task‐based paradigms (Gruber et al, ; Strakowski, Adler, Holland, Mills, & DelBello, ; Thermenos et al, ; Townsend & Altshuler, ). In most studies, irregularities were registered in the frontal lobes along with temporal and subcortical regions such as hippocampus and basal ganglia.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…These findings indicate that the aforementioned nodes are more integrated into the brain network of BD patients than in networks of individuals not suffering from BD, possibly leading to a disturbed perception of emotions in BD. Changes in the limbic system supporting our results were both found in resting‐state paradigms (Ambrosi et al, ; Anand et al, ; Lois, Linke, & Wessa, ; Wang, Wang, Jia, Zhong, Zhong et al, ) as well as in task‐based paradigms (Gruber et al, ; Strakowski, Adler, Holland, Mills, & DelBello, ; Thermenos et al, ; Townsend & Altshuler, ). In most studies, irregularities were registered in the frontal lobes along with temporal and subcortical regions such as hippocampus and basal ganglia.…”
Section: Discussionsupporting
confidence: 87%
“…Overall, comparing our results to other studies utilizing graph theory to examine differences between BD and MDD is difficult as these studies are still rare and results among them vary. While a previous study reported a significantly higher global CC mean value (He et al, ) between a group of BD patients in mixed states (mainly depressed) and a group of acutely depressed MDD patients, another study comparing depressed BD and MDD individuals (Wang, Wang, Jia, Zhong, Zhong et al, ) did not detect any significant differences in global CC. They instead reported significantly higher global PL and lower EF mean values for both acutely depressed BD and MDD patients compared to HC.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations